1998
DOI: 10.1001/archinte.158.8.879
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualizing Advance Care Planning From the Patient's Perspective

Abstract: The traditional academic assumptions are not fully supported from the perspective of patients involved in ACP. The patients we interviewed stated that (1) the purpose of ACP is not only preparing for incapacity but also preparing for death; (2) ACP is not based solely on autonomy and the exercise of control, but also on personal relationships and relieving burdens placed on others; (3) the focus of ACP is not only on completing written advance directive forms but also on the social process; and (4) ACP does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
202
0
9

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 269 publications
(215 citation statements)
references
References 32 publications
4
202
0
9
Order By: Relevance
“…39 Remarkably, ACP is documented considerably more often in The Netherlands than in Belgium, even after controlling for country differences in patient or care characteristics. This country-specific effect might be rooted in a general difference in medical culture between the two countries, as physicians in The Netherlands tend more toward the formalization of practices.…”
Section: Discussionmentioning
confidence: 99%
“…39 Remarkably, ACP is documented considerably more often in The Netherlands than in Belgium, even after controlling for country differences in patient or care characteristics. This country-specific effect might be rooted in a general difference in medical culture between the two countries, as physicians in The Netherlands tend more toward the formalization of practices.…”
Section: Discussionmentioning
confidence: 99%
“…It is consistently reported that, rather than promoting personal preferences and autonomy, a key motivator for ACP is patients' desire to relieve family members of the burden of care and responsibility for making difficult decisions. 65,76,81,82,133 ACP emerges largely as a professional construct framed as an intervention requiring professional mediation. Little is known about the extent or nature of discussions regarding end of life issues that may go on within families, though some studies report patients may look to relatives as well as, and possibly instead of, professionals for this purpose.…”
Section: 114mentioning
confidence: 99%
“…Little is known about the extent or nature of discussions regarding end of life issues that may go on within families, though some studies report patients may look to relatives as well as, and possibly instead of, professionals for this purpose. 43,75,133,134 The availability and willingness of relatives to provide care is critical to enabling death to occur at home. 69,135 Relatives clearly have an important role to play in decisions about ACP and in providing hands-on care for patients dying at home.…”
Section: 114mentioning
confidence: 99%
See 2 more Smart Citations